1985
DOI: 10.1002/ijc.2910360507
|View full text |Cite
|
Sign up to set email alerts
|

HTLV‐I is endemic in Southern Italy: Detection of the first infectious cluster in a white population

Abstract: Human T-cell leukemia virus (HTLV-I) infection is observed among black and Japanese populations in well-delimited endemic spots in association with a high incidence of adult T-cell leukemia (ATL). We present evidence of HTLV-I infection in two ATL patients from southeastern Italy who have not travelled and who have no known relations abroad, and in 8% of non-leukemic controls from the same area. Thus, populations exhibiting HTLV-I infection appear more widespread than supposed up to now.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1
3

Year Published

1986
1986
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 14 publications
0
22
1
3
Order By: Relevance
“…After the first report, which indicated a possible endemicity of HTLV-I in Apulia (Manzari et al, 1985), subsequent serosurveys on blood donors from this region failed to evidence any reactivity to HTLV-1/11 (De Stasio et aL, 1990). A seroprevalence of 0.034% in Italian blood donors has been reported (Lee et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…After the first report, which indicated a possible endemicity of HTLV-I in Apulia (Manzari et al, 1985), subsequent serosurveys on blood donors from this region failed to evidence any reactivity to HTLV-1/11 (De Stasio et aL, 1990). A seroprevalence of 0.034% in Italian blood donors has been reported (Lee et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
“…In Italy, a prevalence rate of 8% for HTLV-I was initially reported in Apulia (southeastern Italy), which was considered an endemic area (Manzari et al, 1985). Further studies have not confirmed these data (De Stasio et al, 1990), showing that no HTLV-1/11 reactivity was present in local populations, with the exception of IVDU in whom a seroprevalence rate of 1.5% was reported (Quarto et al, 1989).…”
mentioning
confidence: 92%
“…There is no known HTLV-I endemic area in Europe; early reports from southern Italy (Manzari et aL., 1985) are disputed (de Stasio et al, 1989;Chironna et al, 1994) and most cases of HTLV -1 infection have been in immigrants from the West Indies, Africa or the Middle East, or in persons who had sexual relationships with such immigrants (Cruickshank et al, 1989;Wyld et al, 1990;Taylor, 1996). However, sporadic cases of HTL V -1 infection without evidence of a link with an endemic area have been reported in Greece (DaIekos et al, 1995), Romania (Paun et al, 1994), Georgia (Sen juta et al, 1991), SiciIy (Boeii et al, 1995;Mansueto et aL., 1995) and the United Kingdom (Wyld et al, 1990).…”
Section: And Northernmentioning
confidence: 99%
“…HTLV-I infections are reported worldwide with foci in Japan, the Philippines, the Caribbean, Southern Italy, the Arctic area, Brazil, and the African continent [Hinuma et al, 1982;Okochi et al, 1984;Ishida et al, 1988;Bartholomew et al, 1985;Manzari et al, 1985;Cortes et al, 1989;Saxinger et al, 1984 Group, 1989; Delaporte et al, 1989;Schmutzhard et al, 19891.…”
Section: Introductionmentioning
confidence: 97%